Adult Attachment Styles and Psychosocial Health - Ludwikowska-Świeboda, Karolina (Journal of Education, Health and Sport, 2022)
Introduction Early relationship experiences with parents or other important caregivers provide the matrix on which people form subsequent bonds in their lives. An attachment style relates to how people perceive themselves and significant others in terms of the possibility of obtaining support and care in stressful situations. There can be distinguished a secure attachment style and three insecure patterns of bond: preoccupied, dismissing and fearful (or disorganized). Psychosocial functioning of individuals with particular attachment styles is related to mental health in adulthood. Purpose The aim of this paper is to discuss the relationship between different attachment styles and mental health (in the context of emotional regulation, coping with stress, the quality of interpersonal relationships and the prevalence of mental disorders). The state of knowledge A secure attachment style is positively related to the mentalization ability and fosters forming more satisfying interpersonal relationships. People with a secure attachment style cope better in stressful situations and are less likely to develop depression and anxiety disorders. People with insecure attachment patterns use less social support as an effective coping strategy. Insecure attachment styles are also a risk factor for depression and anxiety disorders. Conclusions Professional support aimed at people characterized by insecure attachment styles is very important in the context of developing the ability to form close and satisfying interpersonal relationships, and in the context of mitigating the symptoms of mental health disorders.